2019
DOI: 10.1149/2.0381905jes
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet-Printed Reduced Graphene Oxide (rGO) Films For Electrocatalytic Applications

Abstract: Reduced graphene oxide (rGO) films for application as electrocatalyst have been deposited using an inkjet materials printer, with excellent control over the film morphology and properties. The dispersions were prepared by the ultrasound-assisted liquid exfoliation method using polyvinylpyrrolidone (PVP) as stabilizer. The environmentally friendly ink formulation exhibits a stability for at least 6 months. The inkjet-printed rGO/PVP composite films were thermally treated at different temperatures, and it was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Controlling the flake size distribution is crucial to avoid nozzle clogging and complications during printing. Additionally, the dispersant-to-graphene ratio, which determines the surface coverage of graphene flakes by dispersants, is critical for optimizing charge transport in graphene films [ 7 ], and flake size distribution [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Controlling the flake size distribution is crucial to avoid nozzle clogging and complications during printing. Additionally, the dispersant-to-graphene ratio, which determines the surface coverage of graphene flakes by dispersants, is critical for optimizing charge transport in graphene films [ 7 ], and flake size distribution [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different studies on IJP with graphene-based inks have been carried out, mainly for applications in electronic, bioelectronic, and energy storage [ 185 , 186 , 187 , 188 , 189 , 190 ]. For example, Li et al reported an easy IJP method for the fabrication of micro-supercapacitors (MSCs) based on graphene and printed on various substrates.…”
Section: Additive Manufacturing For Graphene-based Materialsmentioning
confidence: 99%
“…In addition, graphene-based electrodes are readily fabricated using graphene inks and printed onto substrates. [94][95][96] This approach has been employed to produce graphene-based cathodes. 82,85 In a recent study, a graphene ink-coated cathode was shown to give rise to a near doubling of the amount of H 2 O 2 generated.…”
Section: Graphene-based Composites and Electrodesmentioning
confidence: 99%